(untitled) (Journal of Academic Finance, 2023)
Purpose: This article aims to analyze the effects of holding specific assets on the choice of financing methods by Cameroonian manufacturing companies. Approach: An exploratory study made it possible to characterize the specific assets of the prospected entities. The verification of research hypotheses required a questionnaire administered to some industrial companies. The data collected was subjected to multiple linear regression analyses. Results: Reputation has a positive and significant impact on capital growth. On the other hand, human capital and R&D have a negative impact on debt financing, unlike outsourcing. Originality: The paper has the originality of examining the specificity of assets in the context of SME. It highlights the reality that assets specificity influence funding sources.